2013
DOI: 10.1177/0961203313492577
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of current treatments for systemic lupus erythematosus: a patient and physician survey

Abstract: An independent cross-sectional survey assessed systemic lupus erythematosus (SLE) disease and treatment burden. Variables included medication classes prescribed, disease activity, flare occurrences, treatment satisfaction, and validated measures of health-related quality of life (HRQoL), fatigue and work productivity. Of 886 eligible patients (mean age 41.3 years, 89% female), 515 completed the survey. One-third reported moderate-to-severe disease activity, and 31% had flared in the last 12 months. Higher seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
(43 reference statements)
0
21
1
Order By: Relevance
“…In terms of age, sex, and ethnicity, the demographic profile of the patients participating in these studies were consistent with those of other belimumab studies 4,5,7,12 and a previous survey of physicians and patients with SLE that investigated treatment burden. 13 According to physician assessment, in both studies most patients had moderate or severe disease and deteriorating or unstable disease before treatment initiation. In the LPP, 82.9% of physicians and 86.3% of patients were at least somewhat satisfied with belimumab-containing regimens.…”
Section: Discussionmentioning
confidence: 98%
“…In terms of age, sex, and ethnicity, the demographic profile of the patients participating in these studies were consistent with those of other belimumab studies 4,5,7,12 and a previous survey of physicians and patients with SLE that investigated treatment burden. 13 According to physician assessment, in both studies most patients had moderate or severe disease and deteriorating or unstable disease before treatment initiation. In the LPP, 82.9% of physicians and 86.3% of patients were at least somewhat satisfied with belimumab-containing regimens.…”
Section: Discussionmentioning
confidence: 98%
“…Fatigue and pain were identified as two of the most important and frequent symptoms for patients with SLE [24]–[26],[29]–[32] (Figure 1). Specifically, patients describe mental and physical symptoms of fatigue including impacts on social life [24], emotional wellbeing [24],[33], physical functioning [22],[24], sleep [31],[34]–[36] and the ability to complete daily tasks and leisure activities [27],[28].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, patients have difficulty maintaining family and sexual relationships [24],[26],[37]. SLE also impacts negatively on patients’ career progression [25], absence from work [22], difficulty concentrating at work or study [22],[26],[32] and their choice of work [26],[27]. …”
Section: Resultsmentioning
confidence: 99%
“…The EQ-5D has been primarily used in clinical SLE research studies [47-51]. For example, Strand and colleagues found that SLE patients taking corticosteroids had lower HRQOL, measured by the EQ-5D, than those who were not taking corticosteroids, and concluded that medication side effects contribute to poorer HRQOL in these patients [50]. EQ-5D was also included in the belimumab clinical trials, with changes in patient-reported pain/discomfort domain noted [38].…”
Section: Generic Pro Instrumentsmentioning
confidence: 99%